1978
DOI: 10.1039/p29780000217
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of ten-membered-ring sesquiterpenes. Crystal and molecular structures of agerol diepoxide and ageratriol

Abstract: The crystal and molecular structures of agerol diepoxide (3) and ageratriol (2), which have been determined by direct methods and refined by least-squares to R 0.060 and 0.069 respectively, confirm the previously suggested biogenetic scheme from agerol (1 ). Theoretical calculations by a molecular mechanics method ( G E M 0 program) show that the conformers observed in the crystals have the lowest strain-energy. N.m.r. measurements indicate that agerol diepoxide adopts this conformation also in solution.AGEROL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The structures of agerol diepoxide and ageratriol, established by X-ray analysis by Messerotti et al (287), confirmed the previously suggested biogenetic scheme from agerol.…”
Section: Buttkus Et Al (supporting
confidence: 84%
“…The structures of agerol diepoxide and ageratriol, established by X-ray analysis by Messerotti et al (287), confirmed the previously suggested biogenetic scheme from agerol.…”
Section: Buttkus Et Al (supporting
confidence: 84%
“…and 'H n.m.r. spectra with those of the authentic specimen prepared by isonierization of the natural (4-)-bicyclogermacrene (25), an enantiomer of ( -)-enr-bicyclogermacrene (4)." The geometries of the two double bonds were alternatively shown to be C(I)-C(l0) trans and C(4)-C(5) cis on the basis of n.0.e.…”
mentioning
confidence: 99%
“…863 cm-I; 6 1. 25 (3 H, d, J 1.5 Hz) and 5.06 (1 H, m)] and a cyclopropane ring with a gem-dimethyl group [v,,,,,. 1 382 and 1 377 cm-'; 6 0.1-1.1 (2 H, m) and 1.18 and 1.21 (each 3 H, s)].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hz) indicate an anti coplanar relationship between -1 and one of these hydrogens (H-2 or H-2'), i.e., an axiallike orientation for -1. The conformation ofgermacrane derivatives, however, is often very difficult to determine, due to the flexibility of medium-sized rings (17)(18)(19). In the case of compound 1, for instance, an axial-like orientation of -1 can be reached with both possible configurations at C-l.…”
mentioning
confidence: 99%